TEACHING STRATEGIES USED IN INCLUSION SCIENCE CLASSES TO DEVELOP SCIENCE LEARNING OF STUDENTS WITH LEARNING DIFFICULTIES IN PRIVATE SCHOOLS IN DUBAI - AlSadoon, M; Forawi , S (Proceedings of the International Conference on Education, 2023)
One of the most important things for students with LD to do to improve their science learning is for their science teacher to be ready to provide the right adaptations, accommodations, resources, and methods in a general classroom setting. As part of a PhD dissertation, this research paper is meant to look at the strategies’ science teachers use to help students with learning difficulties learn science in the middle grades of private schools in Dubai. The goal is to answer the question, " What practices do science teachers have to develop science learning among students with LD in middle schools in Dubai?" A sequential mixed approach has been used to answer this research question, including a science teacher’s questionnaire and a semi-structured interview of some science teachers. A 33-item questionnaire based on the study had been piloted to test the consistency of the items after they were revised by experts in the education field. 156 science teachers in different private schools in Dubai have responded to the questionnaire. The researcher then held a semi-structured interview with 14 science teachers individually to gain a deeper understanding of their point of view regarding the teaching strategies used in their classes. Except for a few highlighted points, the data collected and independent t-test results show that there are no significant differences in using one strategy over another in science classes. The research study confirmed that in the Dubai context, participants in this survey stressed the need for science teachers to learn about various learning difficulties so they may better understand how to instruct these students, which requires cooperation among all the stakeholders in the educational process to work together with clear goals and strategies to raise the science teachers’ performance.